Small Medium Enterprises approach to leadership and lean during a global pandemic: a case study of Singapore’s tourism industry - Corbett, Richard Corbett (2023)
This study has researched the challenges face by the leaders of SME attractions within the Singapore tourism industry during the global pandemic, known as COVID-19, and how leadership and lean concepts were adopted and/or utilised by the SME attraction leaders in response to these challenges. In describing COVID-19 it is clear that the pandemic has had a catastrophic impact on many industries globally, especially the tourism industry. Singapore, with a small population of just 5.5 million in 2020, reached a high of 19.11 million international visitors in one year in 2019, in which the Singapore tourism industry was very dependent on this visitation and spend. During COVID-19 international visitors was drastically reduced for a long period of time, therefore reduced a major section of revenue opportunity for SME attractions. This study attempts to identify the awareness of leadership and effective leadership styles adopted by SME attraction leaders in the time of crisis (COVID-19), and how lean and the implementation of lean can help to respond to the challenges presented. Research was conducted into a vast array of leadership and lean academic literature, and data was collected through a qualitative research approach, adopted in the format of semi structured interviews targeting SME attractions leaders who were in leadership roles during COVID-19. The research found the main challenges encountered by the SME attraction leaders during COVID-19 to be financial performance, job security and staff motivation. By emphasising the key findings in responses to the challenges found that there was a requirement for SME attraction leaders to adapt their leadership styles to the situation at hand, which identified the need for an adaptive leadership theory that incorporates much more than the transaction style of a one directional change. In addition, the study examined the adoption of lean concepts by the SME attraction leaders, which identified that there is a lack in a formal understanding of the lean concept across the industry. To support and guide SME attraction leaders navigate through a future crisis, the study developed three recommendations for SME attraction leaders to adopt to prepare and navigate through future crisis event. Adaptive leadership practices promote good leadership and effective team performance in different situation impacted by both internal and external environment. The incorporation of the lean fundaments contributes towards a lean strategy gaining a competitive and sustainable profit by eliminating waste. Collaboration with government agencies will help SME attractions to take advantage of support schemes early and effectively during a time of crisis. In conclusion the COVID-19 pandemic has been an important lesson that there is a requirement for SME attraction leaders to be› effectively prepared to navigate and recover through a future crisis events.